Intensification of the process of beverage production from dry fruit raw material of the Republic of Adygea - O. V. Marinenko; I. E. Boyko; S. A. Gisheva; S. R. Shaburov (Новые технологии, 2019)
At present non-alcoholic industry enterprises are increasingly using various plants and fruits with natural healing properties, containing biologically active substances and multivitamin complexes that are useful for human health. The market of soft drinks is expanding due to the development of a new type of product-functional drinks.Functional drinks are characterized by high nutritional and taste value due to the content of easily digestible carbohydrates, mineral compounds, organic acids and biologically active substances.The research is based on the traditional technology used at the enterprises of the Republic for the production of “Shipovnik” and “Boyaryshnik” functional drinks and one of the most promising ways to intensify extraction using ultrasonic treatment.During the experiment extraction schemes from dry fruit raw materials have been studied and the possibility of their use as resource-saving technologies in the production of drinks from dried rosehips and hawthorn have been evaluated.The research methods used: determination of biologically active substances using capillary electrophoresis using Capel 105 “M” system, determination of the content of extractives using an IRF-454B2M refractometer, and an Expert-001 ionometer has been used to determine the pH.Microbiological parameters of the studied samples have been determined according to GOST R 50474-93 and GOST 10444.12-88. The data obtained correspond to norm indicators on the quantitative and qualitative composition of microflora for extracts. A tasting evaluation of the extracts has been carried out.The experimental data have shown the feasibility of ultrasonic extraction which allows the maximum extraction of biologically active substances for functional drinks from nontraditional vegetable raw materials of the RA, as well as to increase microbiological stability of a finished product, thereby extending the implementation period of the functional drink.